Effect of Cutting Position and Growing Media on Rooting of Salad Cucumber (Cucumis sativus L.) Cuttings - U.D.T. Perera (Advances in Technology, 2025)
The influence of cutting position and growing media on the rooting of salad cucumber lateral branches was investigated at the Faculty of Agriculture, University of Ruhuna, Sri Lanka. A 2×3 Factorial Completely Randomized Design, including four replicates, was used to conduct the investigation. Cutting position (basal end and terminal end of the lateral branch) and growing media (coir dust, coir dust: sand (1:1) and sand) were considered as the two factors. Data were recorded as weight of cutting, length of cutting, number of roots per cutting, length of the longest root, fresh weight of roots and dry weight of roots one month after planting. ANOVA was used to analyze the data and SAS software was used to separate the means by the least significant difference (LSD) at a 5% probability level. According to the results, the weight of cutting, length of cutting, and fresh weight of roots resulted in an interaction effect. Basal end cuttings planted in coir dust media yielded the considerably highest fresh weight of roots (0.507 g). In comparison,terminal end cuttings planted in coir dust media recorded the significantly highest weight (13.500 g) and length of cutting (46.125 cm). Cutting position and growing media had a substantial impact on the length of the longest root and the dry weight of roots. The significantly highest length of the longest root (3.432 cm) and dry weight of roots (0.109 g) were observed in basal end cuttings planted in coir dust media. The number of roots per cutting was significantly high in coir dust (3.530) and coir dust: sand (1:1) (3.036) media. Increasing the vine length results in higher yield than increasing the number and weight of roots because salad cucumber has a short life cycle and bears fruits at the vine nodes. Thus, terminal ends of the lateral branches of salad cucumber can be utilized to effectively root in a coir dust medium to obtain planting material for the subsequent crop cycle.